Keterbukaan Diri (Self Disclosure) Penerima Vaksin Covid-19 kepada Petugas Kesehatan dalam Pelayanan Masyarakat - Dessy Andamisari; Wulan Furrie Lenggana; Septa Zahran (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Self-disclosure is one of the important communication skills when establishing relationships and interacting with other people. This study aims to determine the openness of recipients of the COVID-19 vaccine with health workers in serving the community. Using a qualitative approach with interview techniques, observation and documentation. The results showed that self-disclosure (self-disclosure) of covid-19 vaccine recipients with health workers in public health services included aspects, accuracy (communicating to the right people), motivation (desire to be healthy by avoiding post-vaccination risks), time (moment of disclosure). themselves when health workers need information about the health of vaccinated recipients). Attitudes that support interpersonal communication between health workers and recipients of COVID-19 vaccinations include openness (openness about the condition of the recipients of vaccinations), Empathy (a sense of empathy between officers and recipients of vaccinations), support (professional confectionery), Positivity (positive attitude), Equality (the common goal is to support the government's program in stopping the spread of covid-19), Confidence (stability and comfort), readiness (attention to the other person, ready to listen, and respond).